Organizational life-cycle: The characteristics of developmental stages in Russian companies created from scratch - Galina Shirokova (Journal for East European Management Studies, 2009)
Although plenty of organizational life-cycle research in developed countries may be found in the literature, there is a remarkable lack of such research for transition economies like Russia. This article presents the results of 593 Russian entrepreneurial firms surveyed with a focus on organizational lifecycle issues. A model of the life-cycle was developed including three stages: start-up, growth and formalization. It is found that the development of Russian newly established companies is characterized by an unusually slow change of centralization and formalization level as the firm moves from one stage to another and by preserving the owner's control over the firm even after the transition to professional management. – – Obwohl zahlreiche Arbeiten zu organisatorischen Lebenszyklen in den entwickelten Ländern existieren, gibt es einen bemerkenswerten Mangel an solcher Forschung für Transformationsländer wie Russland. Dieser Artikel enthält die Ergebnisse einer Befragung von 593 russischen Unternehmen mit dem Schwerpunkt auf Fragen zum organisatorischen Lebenszyklus. Ein Lebenszyklus-Modell mit drei Stufen wird entwickelt - Gründung, Wachstum und Formalisierung. Es wird festgestellt, dass die Entwicklung der neu gegründeten Unternehmen in Russland beim Übergang von einer Stufe zur nächsten durch eine ungewöhnlich langsame Veränderung bezüglich Zentralisierung und Formalisierungsniveau gekennzeichnet ist und durch das Aufrechterhalten der Kontrolle des Eigentümers über die Firma, selbst nach dem Wechsel zu einem professionellen Management.
Keywords: 650; organisational life-cycle; entrepreneurship; developmental stages; Russia